2012
DOI: 10.1016/j.agee.2011.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Denitrification potential in subsoils: A mechanism to reduce nitrate leaching to groundwater

Abstract: Understanding subsurface denitrification potential will give greater insights into landscape nitrate (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
82
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(91 citation statements)
references
References 71 publications
7
82
1
1
Order By: Relevance
“…This trend in emission is close to the trend of soil NO 3 --N on day 3 both in order and in relative magnitude (Figure 2 Krol et al (2015) who reported 0.9-1.3%. Differing emission factors in other studies could be due to soil type and climatic conditions, which can be important factors affecting N 2 O emissions (Rochette et al, 2008) and its conversion to N 2 , resulting in a lower emission factor (Jahangir et al, 2011;Jahangir et al, 2012). Different fodders, feed additives and grazing regimes may affect N concentrations in urine and dung, which can have a significant effect on N 2 O emissions (Oenema et al, 1997).…”
Section: N 2 O Emissions Over Timementioning
confidence: 94%
See 1 more Smart Citation
“…This trend in emission is close to the trend of soil NO 3 --N on day 3 both in order and in relative magnitude (Figure 2 Krol et al (2015) who reported 0.9-1.3%. Differing emission factors in other studies could be due to soil type and climatic conditions, which can be important factors affecting N 2 O emissions (Rochette et al, 2008) and its conversion to N 2 , resulting in a lower emission factor (Jahangir et al, 2011;Jahangir et al, 2012). Different fodders, feed additives and grazing regimes may affect N concentrations in urine and dung, which can have a significant effect on N 2 O emissions (Oenema et al, 1997).…”
Section: N 2 O Emissions Over Timementioning
confidence: 94%
“…Anaerobic conditions will decrease nitrification whilst altering the N 2 O/N 2 ratio during denitrification. It is also possible that the higher C content added in the dung and the wet soil conditions may have promoted a more complete reduction of N 2 O to N 2 (Jahangir et al, 2012) There is also potential that the applied dung may have increased soil N immobilisation through the addition of large quantities of carbon (Hatch et al, 2000). Very little difference was found between the urine only, the CAN only and the urine & CAN treatments in terms of soil NH 4 + -N content.…”
Section: Net Cumulative N 2 O Emissions: Dung Urine and Can In Combimentioning
confidence: 99%
“…Jahangir et al (2012) found that adding carbon to deeper soil horizons significantly enhances denitrification in those layers. Profiles of dissolved organic carbon (DOC) in deep vadose zones (down to 9 m below ground) under citrus orchards on thick vertisols versus sandy-loam in Israel were compared.…”
Section: Kurtzman Et Al: Soil-aquifer Phenomena Under Vertisolsmentioning
confidence: 96%
“…Some studies have shown that the highest rates of denitrification occur in the upper soil horizon (Kustermann et al, 2010;Jahangir et al, 2012), the extent of which depends on WC and WFPS. Soil WC can impact on many different soil processes such as mineralization, leaching, plant uptake and denitrification (Porporato et al, 2003).…”
Section: Nitrogen Leachate and Soil Propertiesmentioning
confidence: 99%